MOMORDICA CHARANTIA NANO DRY POWDER ORAL FORMULATION IN CONTROLLING HISTAMINE-INDUCED BRONCHOSPASM - KARTHIKA P; BHUVANESWARI K; BALACHANDER R (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Momordica charantia (MC) (bitter gourd) is known traditionally to possess medicinal values. This edible vegetable is known for its anti-inflammatory properties and has been studied for its bronchospasm preventive action. With the recent development in nanoformulations, this study was done to identify the effectiveness of MC nanoformulation in comparison to crude MC formulation in protecting animal from histamine-induced bronchospasm. Methods: The optimized MC nanoformulation was prepared with polyethylene glycol and soy phosphatidylcholine. The MC crude powder was prepared by drying in hot air oven and grinding in a blender. Eight guinea pigs of both sexes were given once daily MC nanoformulation per oral by mixing with water for 7 days. Evaluation of the formulation was done on the 2nd, 4th, and 6th h on day 1 and day 7 after administration of MC for protection in developing pre-convulsive dyspnea due to histamine-induced bronchospasm. Results: An analysis of variance test revealed statistically significant results in the protection of animals from developing bronchospasm after treatment with the MC nanoformulation in comparison to the control values. About 75% of animals were protected from developing bronchospasm on day 7 attributing to the cumulative effect of nanoformulation. Conclusion: The study proved that the MC nanoformulation could effectively prevent histamine-induced bronchospasm in guinea pigs.